Beyond Ipilimumab: a review of immunotherapeutic approaches in clinical trials in melanoma. Issue 1 (18th December 2020) - Middleton, Gary
Summary: In this first in a series of 'Trials Watch' articles, we briefly review a highly selected set of clinical trials that are currently recruiting or about to open to recruitment in melanoma, the disease first transformed by the introduction of immune checkpoint blockade inhibitors (ICI). We place equal emphasis on phase I/II studies investigating the activity of biologically compelling novel immunotherapeutics, and on randomised trials of ICI with and without novel agents, as these latter studies optimise the standard-of-care use of ICI, and determine whether novel agents become part of the approved therapeutic armamentarium. We do not consider here combination therapy with other checkpoint antagonists or agonists besides combination of anti-PD-1/PD-L1 monoclonal antibodies (mAbs) with anti-CTLA4 mAbs, as these will be reviewed in a subsequent article in this series. A glossary of agents to be discussed is found at the end of this article.